2013
DOI: 10.1088/0960-1317/24/2/027001
|View full text |Cite
|
Sign up to set email alerts
|

Stress control of plasma enhanced chemical vapor deposited silicon oxide film from tetraethoxysilane

Abstract: Thin silicon dioxide films have been studied as a function of deposition parameters and annealing temperatures. Films were deposited by tetraethoxysilane (TEOS) dual-frequency plasma enhanced chemical vapor deposition with different time interval fractions of high-frequency and low-frequency plasma depositions. The samples were subsequently annealed up to 930 • C to investigate their stress behavior. Films that were deposited in high-frequency dominated plasma were found to have tensile residual stress after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…These are all aimed at either reducing the reactivity of strained Si-O groups or preventing the diffusion of water to the reactive sites. [29,30] For our present aims, the use of alternating or capping layers is less desirable, since the membranes are in some cases patterned with pores. Moreover, the use of a nitride layer would likely diminish the optical quality of the membrane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These are all aimed at either reducing the reactivity of strained Si-O groups or preventing the diffusion of water to the reactive sites. [29,30] For our present aims, the use of alternating or capping layers is less desirable, since the membranes are in some cases patterned with pores. Moreover, the use of a nitride layer would likely diminish the optical quality of the membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Our general aim in this study is to fabricate a robust and tensile ultrathin (100–300 nm) porous SiO 2 membrane. It has been shown that the film stress of SiO 2 layers from tetraethoxysilane (TEOS, Si(OC 2 H 5 ) 4 )-based plasma-enhanced chemical vapor deposition (PE-CVD) can be controlled through the use of a dual frequency deposition method [28,29]. Alternating layers are deposited with high-frequency (HF, 13.56 MHz) and low-frequency (LF, 50–400 kHz) plasmas using two separate RF power supplies.…”
Section: Introductionmentioning
confidence: 99%
“…No significant changes were observed. Silicon oxide stress can change significantly due to moisture absorption [33,34], potentially leading to curvature variations of oxide structures with time. However, the cantilevers of this work do not leave any oxide exposed to ambient air.…”
Section: F Curvature Versus Timementioning
confidence: 99%
“…For example, by making structure of heat treatment the purpose of minimization stress [7,12]. To determine nature of occurrence of mechanical stresses carried out comparative analysis of stress values and value of thermal stress calculated in TCAD software.…”
Section: Figure 4 the Distribution Of Mechanical Stresses In The Wafermentioning
confidence: 99%